If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7b + 4a + -3a + -5b = 0 Reorder the terms: 4a + -3a + 7b + -5b = 0 Combine like terms: 4a + -3a = 1a 1a + 7b + -5b = 0 Combine like terms: 7b + -5b = 2b 1a + 2b = 0 Solving 1a + 2b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2b' to each side of the equation. 1a + 2b + -2b = 0 + -2b Combine like terms: 2b + -2b = 0 1a + 0 = 0 + -2b 1a = 0 + -2b Remove the zero: 1a = -2b Divide each side by '1'. a = -2b Simplifying a = -2b
| 1.1666x=140 | | 37=5+8x | | 3512/4= | | 11x+3=2x-5 | | X*(2X+5)=25 | | x^3+8x^2-3x-2266=0 | | 4x=3512 | | 1=5(3)+b | | 13x-3y=34 | | 5x^2=2.2x^2+5.88x+3.168 | | 64*3.14= | | 8/6=5/9 | | 3=-1x+1y | | p(5)=1.8 | | n/32=512 | | a^17/4a^9 | | 360=x(x+2) | | 65=2+7x | | 40-2.5x=3 | | 3(p+7)=2(p-3)+p+27 | | h(5)=175(1.028)5 | | 0.4(x-0.45)=9.2 | | 5+8=43 | | Z/5w=8 | | 9=(20/6x) | | 2/3n=46000 | | 6n=432 | | .9=(20/6x) | | 2/3x=46000 | | 4(3y+6)=12-2(y-6) | | 5x^2+25x-44=0 | | 10x-4x+136=10x+64 |